Entre os muros da escola: análise da dimensão subjetiva do espaço escolar - Leite, Ana Carolina dos Santos Martins (2016)
This research addresses the spatial dimension as a basic condition for the effectiveness of teaching with focus on different representations of teachers and students about the school spaces. It is proposed to answer the question: what are the relations between subject’s symbolization / places / territories within that school building? What is the representation of the subject of the space? How to configure these elements? The hypothesis is stipulated that there are different views of these subjects concerning the areas within the school. These differences depend on both the place the individual occupies, as the environment referred to, indicating that the spaces have exercised symbolic powers. Thus, and as a basis for analysis, the research aims to analyze and understand the subjectivity of school space, investigating how teachers and students are manifested on the environment. To this end, we selected a municipal educational unit of the West Zone of São Paulo, characterized as empirical field for research and information gathering. On-site observations were conducted, interviews, questionnaires and drawings, with students in the first and fifth grade of elementary school. Interviews were conducted with teachers of these school years also completed questionnaires. The main concepts used were the space, place and territory based on several authors mainly Viñao Frago and Bourdieu. The data allowed us to understand the influence of different places / areas of the school building on these students and their preferred spaces were routinely perceived teachers, unremembered spaces, usage rules of these environments in relation to the position of the subjects in their own school social space. From the data collected hypothesis was confirmed, as the analysis showed different manifestations of teachers and students on school spaces